2016
DOI: 10.1038/mp.2016.180
|View full text |Cite
|
Sign up to set email alerts
|

In vivo imaging of brain microglial activity in antipsychotic-free and medicated schizophrenia: a [11C](R)-PK11195 positron emission tomography study

Abstract: Positron emission tomography (PET) imaging of the 18 kDa translocator protein (TSPO) has been used to investigate whether microglial activation, an indication of neuroinflammation, is evident in the brain of adults with schizophrenia. Interpretation of these studies is confounded by potential modulatory effects of antipsychotic medication on microglial activity. In the first such study in antipsychotic-free schizophrenia, we have used [C](R)-PK11195 PET to compare TSPO availability in a predominantly antipsych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
81
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 71 publications
8
81
1
Order By: Relevance
“…This could be reversed through antipsychotic medications. The possible antiinflammatory involvement could be illustrated by a recent study (Holmes et al, 2016) using positron emission tomography and radioligands that bind to the 18-kDa translocator protein that shows a direct interaction between antipsychotic medication and microglial activation in medicated patients with schizophrenia. The antiinflammatory effect of antipsychotic treatment may produce microglial activation (Holmes et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be reversed through antipsychotic medications. The possible antiinflammatory involvement could be illustrated by a recent study (Holmes et al, 2016) using positron emission tomography and radioligands that bind to the 18-kDa translocator protein that shows a direct interaction between antipsychotic medication and microglial activation in medicated patients with schizophrenia. The antiinflammatory effect of antipsychotic treatment may produce microglial activation (Holmes et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The possible antiinflammatory involvement could be illustrated by a recent study (Holmes et al, 2016) using positron emission tomography and radioligands that bind to the 18-kDa translocator protein that shows a direct interaction between antipsychotic medication and microglial activation in medicated patients with schizophrenia. The antiinflammatory effect of antipsychotic treatment may produce microglial activation (Holmes et al, 2016). There are 2 possible explanations for this normalization: the direct impact of antipsychotic treatment on the immune system or the indirect effect of antipsychotic treatment on the immune system by the improvement of the clinical symptoms of schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Three of the latter studies, however, used the first-generation radioligand for TSPO, [ 11 C]PK11195, which is known to have several limitations including low signal-to-noise ratio and brain penetration 1719 ; while the Bloomfield and colleagues study used distribution volume ratio (instead of total volume of distribution) as outcome measure which presents important limitations for data interpretation 21 . Also, in the study by Holmes and colleagues, increase in TSPO expression was only observed in medicated schizophrenia, not in drug-naïve patients 18 . It is noteworthy that a recent meta-analysis of individual data of previous PET studies with second-generation radioligands in psychosis suggests an overall reduction of TSPO expression in psychosis 22 .…”
Section: Introductionmentioning
confidence: 91%
“…Currently, positron emission tomography (PET) imaging of mitochondrial 18 kDa translocator protein (TSPO), which measures microglial activation, is the most valid approach for studying neuroinflammation in vivo [48]. Of nine studies that investigated in vivo brain neuroinflammation in schizophrenia to date [46,48,49,50,51,52,53,54,55], four studies reported higher neuroinflammation in medicated schizophrenia patients as compared to healthy volunteers [50,51,53,55]. However, three out of these four studies used a first-generation radioligand for TSPO, [ 11 C]PK11195, which is known to have important methodological limitations.…”
Section: Inflammation and Psychosismentioning
confidence: 99%